A preliminary study on the development of a Filipino emotion questionnaire to measure food-evoked emotions. - Galimpin, Viary Lycerlene O.
Measuring liking alone failed to predict consumer food choice as demonstrated by the failures of newly developed products in the market that previously passed the sensory evaluation. Researchers nowadays focus on the development of emotion questionnaires to measure food-evoked emotions in order to acquire data that can provide information that go beyond liking. The EsSence ProfileTM has been considered as a standard questionnaire to measure emotions and the translated versions are used in order to measure emotions from different countries. However, there is an argument that emotions differ from different language and culture. This study aimed to develop a Filipino emotion (FilMo) questionnaire and compare it with the EsSence ProfileTM. The FilMo questionnaire was developed through internet surveys which generated 28 Filipino emotion words and showed that Filipino food-evoked emotions are different from those emotions in the English-based questionnaire. Both questionnaires showed a limited discriminative ability towards the products due to the products? highly similar sensory characteristics. Over-all liking scores showed that liking and product relationship did not show a significant difference (p=0.230). The words from both questionnaires showed low correlation to liking which indicates that the words are appropriate and can provide further information beyond liking.